2022
DOI: 10.3390/antibiotics11020124
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antimicrobial Use and the Presence of Antimicrobial-Resistant Bacteria on Austrian Dairy Farms—A Pilot Study

Abstract: The assumed link between high levels of antimicrobial use on farms and selection for antimicrobial-resistant (AMR) bacteria on that farm remains difficult to prove. In the pilot study presented here, we analysed total antimicrobial use on 50 dairy farms in Austria and also collected environmental samples to ascertain whether specific AMR bacteria were present. Antimicrobial use (AMU) analysis was based on electronic veterinary treatment records over a one-year period. Faecal samples for the assessment of exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The present study recorded a mean AMU value of 2.504 DDDvet/ cow/year (median 2.580; minimum 0.028 to a maximum of 6.910 DDD vet /cow/year). A previous study from Austria, using a comparable (39). By comparison, in 2007, a study conducted in the United States found that conventional dairy herds had an mean AMU of 5.43 DDD/cow/year (40).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The present study recorded a mean AMU value of 2.504 DDDvet/ cow/year (median 2.580; minimum 0.028 to a maximum of 6.910 DDD vet /cow/year). A previous study from Austria, using a comparable (39). By comparison, in 2007, a study conducted in the United States found that conventional dairy herds had an mean AMU of 5.43 DDD/cow/year (40).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, 22.5% of samples obtained from weaned calves were positive for ESBL/AmpC-producing E. coli. A previous study conducted in Austria in 2017 analyzed voided fecal samples from cowsheds, calf pens and youngstock housing areas, and found that 26% of dairy farms had ESBL/AmpC-producing E. coli present (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies explored the selective effect of the level of AMU and the selection for AMR bacteria in farm animals. However, their results were not conclusive in most cases [60]. Indeed, no studies could demonstrate a significant selective effect on the intestinal population of E. coli following the use of colistin in pigs, whether used at therapeutic or at higher doses [61][62][63].…”
Section: Relationship Between Amu and Amr In Farm Animalsmentioning
confidence: 95%
“…Indeed, no studies could demonstrate a significant selective effect on the intestinal population of E. coli following the use of colistin in pigs, whether used at therapeutic or at higher doses [61][62][63]. This was also not found for cephalosporin resistance mediated by extended-spectrum beta-lactamase (ESBL)-producing (ESBLs) E. coli strains of dairy herd origin [60,64].…”
Section: Relationship Between Amu and Amr In Farm Animalsmentioning
confidence: 99%
“…Surprisingly, the relationship between the use of antibiotics in livestock and the presence of ARB in food has only been established indirectly and remains a contentious subject for study, which does not yield conclusive results [115,116]. This may be due, in part, to the lack of adequate models to study this relationship and because there is a poor understanding of the complex processes that lead to the emergence and spread of AR [115].…”
Section: The Use Of Antibiotics and The Emergence Of Antibiotic Resis...mentioning
confidence: 99%